Analisis Perbandingan Pola Aliran Pada Bangunan Pelimpah Ogee Dan Stepped Dengan Model Fisik 2D - Aditya, Robby Firza; Wahono, Endro Prasetyo; Tugiono, Subuh (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
A spillway building is usually a structure followed by a steep channel. Flow velocity is very dependent on the slope of the bottom channel which causes super critical flow. Besides being fast, the flow in a steep channel also has a considerable energy, so it must be able to be suppressed. The energy reduction in this study was attempted with a stepped spillway. Step weir is a modification of the standard profile for Ogee type weir. This is the background of the author in taking the title of the thesis about Comparative Analysis of Flow Patterns in Ogee and Stepped Overflow Buildings with 2-D Physical Models. The results of this study indicate that the results of the energy line height at the H3 (downstream overflow) point at the upstream height of 3 cm for Ogee are 2.68 cm, and for stepped it is 2.31 cm. There was a decrease in energy by 13.80%. This shows that the stepped spillway can absorb energy better than the Ogee type. The results of observing the flow pattern on the stepped spillway for each increase in the flow rate that overflow in the spillway can be concluded that the flow pattern that occurs is a transition flow to a skimming flow. Keywords: Energy Attenuation, Flow Pattern, Spillway, Stepped Spillway